1991
DOI: 10.1128/jb.173.14.4379-4385.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and high-level expression in Escherichia coli of the Saccharopolyspora erythraea gene encoding an acyl carrier protein potentially involved in fatty acid biosynthesis

Abstract: The erythromycin A-producing polyketide synthase from the gram-positive bacterium Saccharopolyspora erythraea (formerly Streptomyces erythraeus) has evident structural similarity to fatty acid synthases, particularly to the multifunctional fatty acid synthases found in eukaryotic cells. Fatty acid synthesis in S. erythraea has previously been proposed to involve a discrete acyl carrier protein (ACP), as in most prokaryotic fatty acid synthases. We have cloned and sequenced the structural gene for this ACP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…Our results, and those of Hutchinson [10], show that the type II PKS ACPs are clearly poor in vivo substrates for the endogenous E. coli ACPS. This contrasts with the S. erythrae FAS ACP which appears to be a relatively good in vivo substrate of E. coli ACPS [16,17]. In addition otc ACP could also cause substrate inhibition.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…Our results, and those of Hutchinson [10], show that the type II PKS ACPs are clearly poor in vivo substrates for the endogenous E. coli ACPS. This contrasts with the S. erythrae FAS ACP which appears to be a relatively good in vivo substrate of E. coli ACPS [16,17]. In addition otc ACP could also cause substrate inhibition.…”
Section: Resultsmentioning
confidence: 43%
“…The results of Leadlay et al would appear to support this hypothesis. They showed that the heterologous expression of a presumed FAS ACP from the Actinomycete Saccharopolyspora erythrae in E. coli yielded high levels (20 mg 1 _1 ) of predominantly (65%) holo-ACP [16,17]. Clearly in this case CoA and Mg 2+ cannot be limiting.…”
Section: Resultsmentioning
confidence: 99%
“…Such synthases are large, nondissociable, multifunctional complexes which are generally found in yeast and mammalian systems. More recent work has suggested that streptomycetes have a type II FAS; such synthases consist of a series of dissociable enzymes (24,32). The type II FAS is more commonly found in bacterial systems and has been extensively characterized in Escherichia coli (17).…”
mentioning
confidence: 99%
“…Modular systems like erythromycin have a single ACP/module, one for each condensation cycle the growing polyketide chain undergoes before the completed chain is released, so that each ACP domain is used only once in the course of each biosynthetic cycle (11). Most of the Type II systems in bacteria contain a single ACP that works iteratively with other PKS enzymes performing the dual function of receiving the chain extender unit before condensation and of holding the growing polyketide chain after each condensation to produce the polyketide (12,13).…”
mentioning
confidence: 99%